POLA PENGASUHAN DI ASRAMA SEBAGAI PENGEMBANGAN DISIPLIN BELAJAR DAN PEMBENTUKAN KARAKTER ANAK: STUDI KASUS PADA ASRAMA PUTRA SANTO YOSEF KUALADUA, KECAMATAN KEMBAYAN, KABUPATEN SANGGAU, PROPINSI KALIMANTAN BARAT (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
This study aims to determine a clear picture of the extent to which supervised parenting pattern in the St. Joseph Boy Dormitory of Kualadua Village could establish and develop a child's character. The entire device, events and activities in the dormitory indeed are a unity of synergy that can develop the personality or character of its inhabitants. Respondents in this study were current children staying in the dorms and couch of the dorms. Also, parents or guardians of those children, the teachers at the school and the alumni who are scattered in several areas of West Kalimantan and other areas. Researchers can directly meet and interact with boarding children and the coaches whileat the study site. But researchers couldn’t meet the guardians or parents at any time. These parents can be met on holidays while they were visiting the children in the dorm. Researchers tried to see alumni by any communication media. This study used a qualitative approach to the study site in the St. Joseph's Boarding of Kualadua village, Kembayan District, Sanggau, West Kalimantan Province. This special Dormitory for male students from Kualadua Catholic junior high school with experiencesover 60 years (founded in 1952) is managed by the Congregation of MTB Indonesia Brothers. Research method used in this research include observation, interview and documentation. Analysis of the data using qualitative analysis models of Miles and Hubermen. The research shows that (1) children’s interest to attend St. Joseph's dormitory is caused by examples of those who once lived in the dorms and attended Catholic junior Kualadua. (2) The pattern of care that emphasizes togetherness in a dormitory could develop self-reliance and self-esteem. (3) activities and habits of everyday life in the dorm could build learning discipline and self-discipline.